Managing Self-Other Relations in Complaint Sequences: The use of Self-Deprecating and Affiliative Racial Categorizations - Whitehead, Kevin A (Taylor & Francis, 2013)
The production and reception of complaints in talk-in-interaction is shaped by a range of interactional contingencies, including matters of alignment and affiliation between the complainant and complaint recipient(s), and (in cases where the complainee is a person or people) considerations associated the implications of moral failing on the part of complainees. In this report, I describe two complementary practices through which speakers orient to and manage the implications of their racial category membership when acting in the course of complaint sequences. The first of these practices involves speakers’ use of self-deprecating self-categorizations, and the second involves affiliative ways of categorizing or referring to “racial others” (i.e., members of racial categories other than the speaker’s own category). These practices serve as ways in which participants can manage the matters of self-other relations made relevant in the course of complaint sequences.
Keywords: Conversation analysis; Complaint sequences; Membership categorization devices; Racial categories; Self-deprecation; Affiliation